Analisis Pengaruh Pemicu Terhadap Stop Buang Air Besar Sembarangan - Erni Ekawati Marselina; Andi Yusuf; Asrijun Juhanto (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: The government is trying to improve sanitation so that it can run well to support national commitments and achieve the targets of the development agreements of countries in the world. Objectives: To determine the relationship between education, income, latrine facilities, knowledge, attitudes, roles of health workers, roles of community leaders, and the most influential factors in changing open defecation behavior. Methods: The research used a quantitative observational design with a cross-sectional study approach to see the relationship between the independent variable and the dependent variable. Results; show that there is no significant relationship between education, income, the role of community leaders, the role of health workers with changes in open defecation behavior and there is a relationship between latrine facilities, knowledge, and attitudes with open defecation behavior. Conclusion: that knowledge is very influential on changes in defecation behavior. The health officials and community leaders support each other in motivating the community to always maintain sanitation in their environment